HCC Biomarkers in China and Taiwan - Regina M. Santella (Iatreia, 2007)
A number of different types of biomarkers have been used to understand the etiology and progression of hepatocellular cancer (HCC). Perhaps the most well known are the serum/ plasma markers of HBV or HCV infection. These markers include analysis of viral DNA or proteins or antibodies produced against the viral proteins. HBV surface antigen (HBsAg) is most frequently used to determine chronic infection with high or low viral replication, while HBeAg is a measure of chronic infection with high viral replication. Analysis of antibodies includes measurement of anti-HBV core antigen, anti-HBV e antigen and anti-HBsAg. The response to immunization can be monitored by analysis of anti-HBsAg. The other major classes of biomarkers used in studies of HCC are biomarkers of exposure to environmental, lifestyle or dietary carcinogens, biomarkers of oxidative stress and early biologic response. In addition, studies of genetic susceptibility have studied polymorphisms in a number of pathways and their role in HCC risk. The biomarkers of exposure include the measurement of carcinogens in urine and carcinogen-DNA and protein adducts. Examples are measurement of aflatoxin and polycyclic aromatic hydrocarbon metabolites, and DNA and protein adducts. Biomarkers of oxidative stress include urinary isoprostanes and 8-oxodeoxyguanosine and oxidized plasma proteins. Most of these assays are immunologic although the use of high performance liquid chromatograph (HPLC) as well as gas chromatography/mass spectroscopy (GC/MS) have been utilized. In nested case-control studies, many of these markers are associated with elevated risk. For example, elevated aflatoxin and polycyclic aromatic hydrocarbon-albumin adducts, aflatoxin metabolites in urine and urinary isoprostanes were observed in baseline samples from those who went on to develop HCC. Biologic response markers include measurement of specific mutations in the p53 gene. These studies have demonstrated dramatic differences in mutational spectra of HCC depending on the geographic location. Other early response markers measure tumor DNA released into the blood stream. This DNA has been shown to carry the same genetic and epigenetic changes as does the tumor. In particular, detection of mutations in p53 and methylation of a number of tumor suppressor genes including p16, RASSF1A, MGMT, etc have been analyzed. While not yet applied to HCC cases, the area of proteomic and metabolomics may also lead to useful biomarkers of HCC. In terms of genetic susceptibility, a number of investigators are determining whether single nucleotide polymorphisms are related to HCC risk. The genes investigated to date have included those in the carcinogen metabolism, oxidative stress and DNA repair pathways. While definitive studies are still lacking, the data suggest that, in combination with environmental exposures, genetic factors may also be important in HCC risk. The ultimate goal of these biomarker studies is the early identification of high risk individuals so that they can be targeted for enhanced screening or chemopreventive strategies.